Effectiveness of Center of Pressure Trajectory as Anticipatory Postural Adjustment Measurement in Parkinson's Disease With Freezing of Gait History. (April 2023) - Kung, Chien-Feng; Lai, Yun-Ru; Chiu, Wen-Chan; Lien, Chia-Yi; Huang, Chih-Cheng; Cheng, Ben-Chung; Lin, Wei-Che; Chen, Yueh-Sheng; Yu, Chiun-Chieh; Chiang, Yi-Fang; Guo, Yan-Ru; Chen, Yin-Hong; et al.
Background: Evidence showed that patients with Parkinson's disease (PD) who have a history of freezing of gait (FOG) have hypometric anticipatory postural adjustment (APA) during gait initiation (GI) compared to PD without FOG. Objectives: This study aimed to test the feasibility of center of pressure (COP) displacement during GI as the measure of APA in PD with and without a history of FOG. Methods: Patients with PD underwent COP trajectory measurements, including duration, length, velocity, and acceleration in different phases of APA (APA1, APA2a, APA2, and LOC), as well as evaluation of New Freezing of Gait Questionnaire (NFOG-Q), Tinetti balance and gait score, and Postural Instability and Gait Difficulty (PIGD) score in the on and off medication states. Results: The duration (seconds) of APA2a, APA2b, and LOC were highest while velocity in mediolateral direction ( X ) (m/s), including APA1, APA2a, APA2b, and LOC showed lowest in PD with FOG. Velocity in the mediolateral direction in different phases of APA increased in patients with FOG after dopaminergic therapy. APA2a (seconds) and APA2b ( X ) (m/s) were significantly associated with NFOG-Q part II, APA2b ( X ) (m/s) was significantly associated with NFOG-Q part III, and APA2a (seconds) was significantly associated with Tinetti balance and gait and PIGD score. Conclusions: PD with FOG history showed a favorable response of APAs to dopaminergic replacement. The APA parameters by COP trajectory, especially lateral COP shift toward the stance foot (APA2b ( X ) (m/s) and APA2a (seconds)) are surrogate markers to assess PD with FOG history.